Enhancing Phlebitis Detection In Paediatric Patients Through Routine Physician Inspections-A Prospective Observational Study - Rohit, Malraj Sai; V R, Sudha Reddy (Journal of Neonatal Surgery, 2025)
Background: Phlebitis (inflammation of the vein) is a common complication of peripheral intravenous (IV) cannulation, particularly among the pediatric population .Its prompt recognition is essential to avoid complications such as thrombophlebitis, bloodstream infections, and increased length of stay. Although nurses routinely monitor IV sites, doctors inspecting the IV sites may improve detection of phlebitis and minimize negative outcomes associated with the complication. Objective: To assess the impact of a routine physician inspection of the peripheral IV site on the identification of phlebitis in hospitalized children at a tertiary care hospital and to determine risk factors related to the condition. Methods: Twenty-four month prospective observational study was conducted at R.L. Jalappa Hospital & Research Centre. A total of 237 children (aged 1 month to 12 years) requiring IV cannulation were included. Phlebitis was determined using the Visual Infusion Phlebitis (VIP) score, and nurses monitored once every 8 hours (3 times daily) and doctors inspected twice daily. The FLACC and Wong-Baker pain scores were used when appropriate. Results:A total of 237 children were assessed, with phlebitis diagnosed in 33 samples (13.92%). The nurse detected 14 phlebitis cases (5.9%), and the doctor identified 19 phlebitis cases; however, the statistical significance showed that the number of cases the doctor identified was higher than the number of samples the nurse identified (p < 0.05). More phlebitis was observed in younger children (≤3 years). Conclusion: Regularly performed physician inspection was superior to nursing alone in detecting phlebitis in children. Since younger children are more likely to develop phlebitis, monitoring is vital. There is a need to explore a dual surveillance model that incorporates nursing and physician assessment to prevent diagnosis from being missed. It is expected that the clinical outcome will also improve..